A case of acute renal failure caused by paroxysmal nocturnal hemoglobinuria - Soejima, Yoshiyuki; Nakashima, Ken; Sakabe, Takefumi; Takeda, Yoko; Tateishi, Akio; Yamamoto, Midori (Japanese Journal of Reanimatology, 1999)
We have experienced a case of acute renal failure caused by paroxysmal nocturnal hemoglobinuria, in which blood purification therapy was effective. A 44-year-old male patient complained abdominal pain with fever and cough 2 days before his admission. He was anuretic complicated with severe hemolytic crisis. Steroid pulse therapy, administration of haptoglobin, and volume loading with diuretics all failed to improve oliguria. Con-tinuous hemodiafiltration (CHDF) was started on ICU Day 1, followed by continuous equilibration peritoneal dialysis (CEPD) on Day 11. The patient was placed on ventilator, and was successfully weaned from it at 18 th day. Then, he regained normal urinary output, and per-itoneal dialysis was discontinued on Day 21. The concentration of C 3 a in post-hemofilter blood was less when polyacrylonitrile (PAN) was used than when polymethyl methacrylate (PMMA) was used. Acute renal failure is not frequently associated with paroxysmal nocturnal hemoglobinuria. With this patient, upper respiratory tract infection would trigger severe hemolytic crisis, and dehydration from fever and vomiting exacervated his physical condition, leading to acute renal failure. Early intensive care with CHDF/CEPD provided favorable outcome for this patient.